2019
DOI: 10.3389/fphar.2019.00926
|View full text |Cite
|
Sign up to set email alerts
|

Study on Metabolic Trajectory of Liver Aging and the Effect of Fufang Zhenzhu Tiaozhi on Aging Mice

Abstract: The aim of this study was to investigate the metabolic trajectory of liver aging, the effect of FTZ against liver aging in aging mice, and its mechanism using ultraperformance liquid chromatography/quadrupole-time-of-flight mass spectrometry (UPLC-Q-TOF/MS). Methods: A total of 80 C57BL/6J Narl mice were randomly divided into five groups: 3-month-old group, 9-month-old group, 14-month-old group, 20-month-old group, and FTZ treatment group (20 months old). The mice in the treatment group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…On the one hand, this protein expression reached significantly high levels in the WT old group compared to the WT young group. These data agree with those of a recent investigation in which different groups of mice in a progressive state of aging increased their levels of fatty acids and triglycerides in parallel to the older age [ 17 ]. As for the groups of KO NLRP3 mice, especially the group of old mice, there was a significantly reduced FASN protein levels compared to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…On the one hand, this protein expression reached significantly high levels in the WT old group compared to the WT young group. These data agree with those of a recent investigation in which different groups of mice in a progressive state of aging increased their levels of fatty acids and triglycerides in parallel to the older age [ 17 ]. As for the groups of KO NLRP3 mice, especially the group of old mice, there was a significantly reduced FASN protein levels compared to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…Following results from our RNA-seq data and reports that age leads to impaired lipid metabolism, 30 , 31 , 32 , 33 we were able to confirm a significant increase of lipid content in aged livers, however, Cldn3 -/- mice had a lower lipid content compared with Cldn3 +/+ mice ( Figure 4 J ) as we observed previously in young animals ( Figure 3 E–G ). For further validation of the inflammatory phenotype that our gene expression data indicated ( Figure 4 G and H ), we showed that the frequency of total hepatic lymphocytes increased with age in both groups ( Figure 4 K ).…”
Section: Resultssupporting
confidence: 86%
“…It has been well described that senescence-related events that come with advanced age lead to increased accumulation of lipids and triglycerides in the liver. 30 , 31 , 32 We first compared liver tissue of 12-week-old and 52-week-old mice and did not observe a change in hepatic claudin-3 protein levels resulting from age ( Figure 4 A ). The bodyweight of Cldn3 +/+ vs Cldn3 -/- mice was similar over time, while the liver-to-bodyweight ratio of 52-week-old Cldn3 -/- mice was slightly higher ( Figure 4 B and C ).…”
Section: Resultsmentioning
confidence: 99%
“…In the liver, ageing results in changes to its structure and function, including steatosis, fibrosis and altered regeneration, protein synthesis and autophagy [122][123][124][125][126]. The lipid metabolism capacity of the liver declines with age, and in mice steatosis is already observed after 12 months of age [127,128]. These changes not only impair the metabolic capacity of the liver but are also a major risk factor for the development of several chronic diseases, from degenerative disorders to cancer [129].…”
Section: Ageing In Cholestatic Diseasesmentioning
confidence: 99%